Type D personality and self-esteem in conversion disorder: a case-control study - Kılıçaslan, Aslı Kazğan; Yildiz, Sevler; Kurt, Osman; Korkmaz, Sevda (My University, 2021)
Aim: In the present study, we aimed to investigate the differences in type D personality and self-esteem between patients with conversion disorder (CD) and the control group. Material and Method: We carried out the study with 100 patients diagnosed with CD and 100 matching healthy individuals. We used a sociodemographic information form, the Type D Personality Scale (DS-14), and the Rosenberg Self-Esteem Scale (RSES) as the data collection tools. Considering that the scales should have high discriminative powers, we calculated the cut- off points on each scale performing the ROC analysis. Results: The results showed that the patients with CD had significantly higher negative affectivity (NA), social inhibition (SI), and DS-14 total scores than the control group (p<0.001). Also, the patient group obtained significantly higher scores on the RSES than the control group, indicating lower self-esteem among the patients (p<0.001). Finally, we concluded significant positive correlations between the RSES scores and NA (r=0.549 p<0.001), SI (r=0.410 p<0.001) and DS-14 total scores (r=0.521 p<0.001). Conclusion: Overall, we found that CD patients had type D personality traits and low self-esteem. As the patients had decreased self-esteem, their DS-14 scores increased. Uncovering SI and NA to be high in these patients may drive physicians to take measures to mitigate these situations and adopt a different perspective on CD. In addition, the results may contribute to better addressing patients’ conversion symptoms and personality traits compatible with CD.
Keywords: Self-esteem; Conversion disorder; type D personality